Sana Al-Tajweed - Ahmad, Salmiah; Altalmas, Tareq, M.; Nik Hashim, Nik Nur Wahidah; Embong, Abd Halim; Sediono, Wahju; Hassan, Surul Shahbudin (2021)
Sana AI-Tajweed is an Automated system based on a classification approach. It uses classification methods and various acoustic features to evaluate the points of articulation (Makhrai) and characteristics ( Sifaat) of the Quranic letters.